The routledge handbook of media use and well-being - Reinecke, Leonard (Libros electrónicos en Ebscohost, 2016)
The Routledge Handbook of Media Use and Well-Being serves as the first international review of the current state of this fast-developing area of research. The volume provides a multifaceted perspective on the beneficial as well as the detrimental effects of media exposure on psychological health and well-being. As a'first-mover,'it will define the field of media use and well-being and provide an essential resource for research and teaching in this area. The volume is structured along four central considerations: Processes presents concepts that provide a theoretical bridge between media use and well-being, such as psychological need satisfaction, recovery from stress and strain, self-presentation and self-enhancement, or parasocial interactions with media characters, providing a comprehensive understanding of the underlying processes that drive psychological health and well-being through media. Moderators examines both risk factors that promote negative effects on well-being and protective factors that foster positive media effects. Contexts bridges the gap between theory and'real life'by illustrating how media use can influence well-being and satisfaction in very different life domains, covering the full spectrum of everyday life by addressing the public, private, and work spheres. Audiences takes a look at the influence of life phases and life situations on the interplay of media use and well-being, questioning whether various user groups differ with regard to the effects of media exposure. Bringing together the expertise of outstanding international scholars from multiple disciplines, including communication, media psychology, social psychology, clinical psychology, and media education, this handbook sheds new light on the role of media in influencing and affecting emotions.